FACTORS INFLUENCING JOB RETENTION OF PROFESSIONAL – LEVEL SAFETY OFFICERS IN PHRA NAKHON SI AYUTTHAYA PROVINCE - Thaitham , Suphansa; Someran , Laddawan (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2026)
This study aimed (1) to examine the levels of organizational commitment, perceived organizational support, work–life balance, and job retention, and (2) to analyze the influence of organizational commitment, perceived organizational support, and work–life balance on job retention among professional-level safety officers in Phra Nakhon Si Ayutthaya Province. The sample consisted of 280 professional-level safety officers selected through simple random sampling. Data were collected using a seven-point Likert-scale questionnaire and analyzed using descriptive statistics and multiple regression analysis. The results indicated that the overall levels of organizational commitment, perceived organizational support, work–life balance, and job retention were high. The multiple regression analysis revealed that work–life balance in terms of satisfaction (β = 0.32) and time (β = 0.21), perceived organizational support in terms of fairness (β = 0.22), and organizational commitment in terms of continuance commitment (β = 0.20) significantly influenced job retention at the 0.001 level. In addition, normative commitment had a significant effect on job retention at the 0.01 level (β = 0.18). The findings of this study provide empirical evidence that organizational fairness, work–life balance, and career-related stability are critical mechanisms for enhancing job retention among professional-level safety officers. These insights can be applied to the development of effective human resource management strategies and policies aimed at strengthening workforce stability in safety-related professions.